2014
DOI: 10.5007/2175-7925.2014v27n2p1
|View full text |Cite
|
Sign up to set email alerts
|

Lipid content of marine microalgae Chaetoceros muelleri Lemmermann (Bacillariophyceae) grown at different salinities

Abstract: ResumoTeor lipídico da microalga marinha Chaetoceros muelleri Lemmermann (Bacillariophyceae) cultivada em diferentes salinidades. A produção e armazenamento de lipídios por microalgas em resposta a variações nos fatores ambientais são específicos para cada espécie de microalga. O presente trabalho teve como objetivo avaliar o crescimento e a concentração de lipídios totais da microalga Chaetoceros muelleri cultivada em três diferentes salinidades (15, 25 e 35). O experimento foi realizado em triplicatas, utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
3
6
0
Order By: Relevance
“…ml -1 . This is similar with the research conducted by Barros et al which showed that the optimal growth of C.muelleri in his research occurs in salinity 25 ppt [2].…”
Section: Lipid Extractionsupporting
confidence: 92%
See 2 more Smart Citations
“…ml -1 . This is similar with the research conducted by Barros et al which showed that the optimal growth of C.muelleri in his research occurs in salinity 25 ppt [2].…”
Section: Lipid Extractionsupporting
confidence: 92%
“…The lipid content in this phase is the highest compared to other phases. According to Barros et.al, the lipid content will increase dramatically in the stationary phase along with decreasing levels of nitrogen and silicates [2]. However, in continuous cultures, nutrient flow is always constant every day so that increased lipids during this phase are thought to be due to the cell's response to salinity.…”
Section: Lipid Content Chaetoceros Muellerimentioning
confidence: 99%
See 1 more Smart Citation
“…Microalgal cell growth was monitored by measuring the OD 700 in a spectrophotometer (Rial et al, 2013;Shing et al, 2013;Barros et al, 2014). Microalgal cell dry weight concentration was calculated based on an optical density versus cell dry weight calibration curve.…”
Section: Determination Of Cell Dry Weight Concentration and Growth Ratementioning
confidence: 99%
“…Therefore, cultivating microalgae for obtaining not a single but multiple benefits simultaneously is receiving growing attention [ Chaetoceros muelleri is a marine diatom that is ubiquitously distributed worldwide. Because of its fast growth and easy maintenance, C. muelleri has been used in aquaculture as feed for zooplankton and shrimp larvae at commercial hatcheries in many regions [Wang et al 2014 Another reason that C. muelleri has been frequently used in aquaculture is its adaptation to salinity change [Fujii et al 1995;Barros et al 2014;Rahmadi et al 2020], which is likely to often occur in the land-based aquacultural ponds. Though the growth of Chaetoceros spp.…”
Section: Introductionmentioning
confidence: 99%